(untitled) (Plant Tissue Culture and Biotechnology, 2023)
The coastal area of Bangladesh is affected by soil salinity which threatens rice production. Saline soils are mainly caused by excessive Na+ which interferes with the uptake of the essential nutrient K+. Certain K+ transporters may cause leakage of Na+ ions and the OsAKT1 transporter was earlier shown to be downregulated under salt stress in a tolerant rice landrace called Horkuch. We therefore targeted this gene for Crispr-mediated downregulation by Agrobacterium-mediated in planta transformation in salt sensitive IR29 rice. The gene was shown to be significantly downregulated in at least 3 independent transformants. One of the gene edited IR29 transformants showed significantly high survival, low loss in chlorophyll content, low electrolyte leakage as well as low H2O2 after 15-days of salt stress at 120mM NaCl at the T3 generation. Therefore the potassium transporter OsAKT1 gene is a good target for downregulation to produce salt tolerant rice. Plant Tissue Cult. & Biotech. 33(1): 71-84, 2023 (June)